An Overview of the Theory of Instances Computational Complexity - Ruiz-Vanoye, Jorge A; Diaz-Parra, Ocotlan (International Journal of Combinatorial Optimization Problems and Informatics, 2011)
The theory of the computational complexity is a subject of international interest of scientific, technological and enterprise organizations. The computational complexity contains diverse elements such as the classes of problems complexity (P, NP, NP-hard and NP-complete, and others), complexity of algorithms (it is a way to classify how efficient is an algorithm by means the execution time to solve a problem with the worst-case input), complexity of instances (it is computational complexity measures to determine the complex of the problems instances), and others elements. This work is focused on presenting a review of the theory of instances computational complexity.